2021
DOI: 10.5114/ceh.2021.104631
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects and treatment of hepatocellular carcinoma in north-eastern Poland

Abstract: Aim of the study: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer, with poor treatment outcomes often because of delayed diagnosis. The aim of this study was to assess the co-incidence of cirrhosis, alcohol abuse, hepatitis B virus (HBV) or hepatitis C virus (HCV) infection and fatty liver disease in patients in the population of north-eastern Poland, to analyse the usefulness of α-fetoprotein (AFP) in the diagnosis of HCC and to assess the effectiveness of HCC treatment in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Our ndings are closely related to those of Si et al, who found that serum levels of AFP and PIVKA-II in patients diagnosed with HCC due to HBV, but not selected for OLT, were signi cantly associated with tumor size (32). However, in our study, neither serum PIVKA-II nor AFP levels correlated with the number of tumours, in line with other studies such as that of Feng et al who found no correlation between serum PIVKA-II levels and the number of tumours (30), or Lapinski et al who also found no signi cant association between serum AFP levels and the number of tumour nodules (33).…”
Section: Discussionsupporting
confidence: 84%
“…Our ndings are closely related to those of Si et al, who found that serum levels of AFP and PIVKA-II in patients diagnosed with HCC due to HBV, but not selected for OLT, were signi cantly associated with tumor size (32). However, in our study, neither serum PIVKA-II nor AFP levels correlated with the number of tumours, in line with other studies such as that of Feng et al who found no correlation between serum PIVKA-II levels and the number of tumours (30), or Lapinski et al who also found no signi cant association between serum AFP levels and the number of tumour nodules (33).…”
Section: Discussionsupporting
confidence: 84%
“…In recent years, a decrease in the incidence of HBV has been recorded in endemic countries thanks to the vaccination of children. A further reduction in the incidence of HCC can be expected with the use of orally administered drugs inhibiting the HBV replication activity [ 62 ].…”
Section: Primary Liver Cancermentioning
confidence: 99%
“…A factor that hinders the characterization of focal lesions is the pathologically “remodeled” liver parenchyma. Interestingly, in the case of HCC, for the first time in the history of clinical oncology, in 2001, in Barcelona, the EASL expert panel established the criteria for the diagnosis of malignant neoplasm solely on the basis of imaging tests and additional examination of serum AFP (alpha fetoprotein) concentration without the need for histological verification [ 62 ].…”
Section: Primary Liver Cancermentioning
confidence: 99%
“…Chronic carriers have a more than 100-fold increased relative risk of tumor development. Several mechanisms have been proposed to induce HCC using HBV [ 2 ]. HBV causes 80% of liver cancer cases and is the second most common carcinogen after smoking.…”
Section: Introductionmentioning
confidence: 99%
“…HBV causes 80% of liver cancer cases and is the second most common carcinogen after smoking. Babies born to e-positive mothers have approximately a 90% risk of becoming persistent carriers after perinatal infection, and preschoolers have a 30% risk [ 2 , 3 ]. Only 5% to 10% of adults become persistent carriers after infection.…”
Section: Introductionmentioning
confidence: 99%